Long-Term Safety and Antihypertensive Effects of Renal Denervation: Current Insights - Reyes KR; Rader F (Integrated Blood Pressure Control, 2023)
Klevin Roger L Reyes, Florian Rader Smidt Heart Institute, Cedars-Sinai Medical Center, Los Angeles, CA, USACorrespondence: Florian Rader, Hypertension Center of Excellence, 127 San Vincente Blvd. AHSP A3408, Los Angeles, CA, 90048, USA, Tel +1 310 423-3880, Fax +1 310 967-3805, Email Florian.Rader@cshs.orgAbstract: Hypertension is the most potent modifiable risk factor for the development of cardiovascular morbidity and mortality worldwide. Nevertheless, blood pressure (BP) control on a broad scale appears to be insurmountable and has even worsened in the US. Barriers to sustained hypertension control are multifactorial and although lack of patient awareness and socioeconomic barriers to healthcare access may play a role, medication non-compliance and therapeutic inertia are major causes. Renal denervation (RDN) is a minimally invasive procedure that has been the subject of interest in clinical trials for more than a decade and although the first sham-controlled trial could not detect group difference between treated and untreated hypertensives, subsequent, better designed sham-controlled trials clearly demonstrated the BP lowering effect of RDN, as well as its safety. While to-date, RDN is not available for routine clinical practice, one major requirement for broad implementation is that the BP lowering effect is durable. Therefore, this review will summarize the available long-term data of the different RDN modalities with respect to both effectiveness and safety.Keywords: hypertension, renal denervation, device therapy, blood pressure device, resistant hypertension